A mitogen‐activated protein kinase phosphatase influences grain size and weight in rice. (7th June 2018) - Xu, Ran; Yu, Haiyue; Wang, Junmin; Duan, Penggen; Zhang, Baolan; Li, Jing; Li, Yu; Xu, Jinsong; Lyu, Jia; Li, Na; Chai, Tuanyao; Li, Yunhai
Summary: Grain size and weight are directly associated with grain yield in crops. However, the molecular mechanisms that set final grain size and weight remain largely unknown. Here, we characterize two large grain mutants, large grain8‐1 ( large8‐1 ) and large grain8‐2 ( large8‐2 ). LARGE8 encodes the mitogen‐activated protein kinase phosphatase1 (OsMKP1). Loss of function mutations in OsMKP1 results in large grains, while overexpression of OsMKP1 leads to small grains. OsMKP1 determines grain size by restricting cell proliferation in grain hulls. OsMKP1 directly interacts with and deactivates the mitogen‐activated protein kinase 6 (OsMAPK6). Taken together, we identify OsMKP1 as a crucial factor that influences grain size by deactivating OsMAPK6, indicating that the reversible phosphorylation of OsMAPK6 plays important roles in determining grain size in rice. Significance Statement: Grain size and weight are crucial for grain yield in crops, but the molecular mechanisms that set grain size and weight remain largely unknown. Here, we show that OsMKP1 influences grain size by deactivating OsMAPK6, indicating that the reversible phosphorylation of OsMAPK6 plays important roles in setting the final size of rice grains.